Promoting Well-Being Among Intercollegiate Student-Athletes: The Impact of Collegiate Sport Business Practices - Laura Kruger (Journal of Applied Sports Management, 2025)
The purpose of this experimental study was to identify if the implementation of an educational gratitude workshop could increase intercollegiate student-athletes’ self-reported perceptions of well-being and reduce stress, considering sport administrators must address rising mental health concerns among athletes. Participants of various sport teams were randomly assigned to an experimental or control group to assess differences among self-reported measures of state gratitude, psychological distress, life satisfaction, athlete burnout, and perceived available support in sport. Statistical significance was found in the data analysis which demonstrated that the workshop was meaningful, and it significantly influenced the experimental group’s perceived available support in sport, emotionally. The data suggests that student-athletes perceive there is not enough emotional support available to them in their sport, and workshops could help. Implementing educational workshops could help collegiate sport administrators meet the needs of student-athletes’ well-being as a cost-effective solution.
Keywords: Athlete; well-being; sport; business; stress